2017
DOI: 10.1186/s12864-017-3801-8
|View full text |Cite
|
Sign up to set email alerts
|

Accurate characterization of the IFITM locus using MiSeq and PacBio sequencing shows genetic variation in Galliformes

Abstract: BackgroundInterferon inducible transmembrane (IFITM) proteins are effectors of the immune system widely characterized for their role in restricting infection by diverse enveloped and non-enveloped viruses. The chicken IFITM (chIFITM) genes are clustered on chromosome 5 and to date four genes have been annotated, namely chIFITM1, chIFITM3, chIFITM5 and chIFITM10. However, due to poor assembly of this locus in the Gallus Gallus v4 genome, accurate characterization has so far proven problematic. Recently, a new c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…One family of ISGs that functions as broad-spectrum inhibitors of viral replication is the interferon-inducible transmembrane protein (IFITM) family. IFITMs are functionally conserved across many species, including birds (912), pigs (13, 14), and bats (13). In most cases, this family of restriction factors blocks infection during virus entry into cells (15), although additional mechanisms have been proposed (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…One family of ISGs that functions as broad-spectrum inhibitors of viral replication is the interferon-inducible transmembrane protein (IFITM) family. IFITMs are functionally conserved across many species, including birds (912), pigs (13, 14), and bats (13). In most cases, this family of restriction factors blocks infection during virus entry into cells (15), although additional mechanisms have been proposed (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the prediction revealed three differences in the IFITM3 protein between mammals and birds. However, this prediction was carried out on limited species of mammals and birds registered in GenBank, further confirmation in recently reported IFITM3 sequences is needed in the future (Bassano et al 2017). In a previous topology study in the human IFITM3 protein, substantial evidence indicated that the human IFITM3 protein favors the cytosolic Nterminus.…”
Section: Discussionmentioning
confidence: 66%
“…The chicken IFITM ( chIFITM ) genes are clustered on chromosome 5, and to date, four genes have been annotated, namely chIFITM1 , chIFITM3 , chIFITM5 and chIFITM10 [ 50 ]. Although not yet annotated in the Gallus gallus reference sequence, studies show the existence of chIFITM2 and suggest a hypothetical genetic structure of the locus based on the human syntenic genome region [ 51 ]. The mammalian IFITM proteins are relatively small (about 130 amino acids) [ 33 ] and share a topology defined by a conserved CD225 domain, consisting of two intramembrane (IM) regions and a conserved intracellular loop (CIL) [ 52 ].…”
Section: Introductionmentioning
confidence: 99%